Taste Learning and Memory: A Window on the Study of Brain Aging - Gámiz, Fernando; Gallo, Milagros (Frontiers in Systems Neuroscience, 2011)
Taste learning exhibits advantages for research on memory brain systems and its reorganization along the life. A review of the effects of aging on taste memory abilities offers a complex picture showing preserved, impaired and enhanced functions. Some of the age-related changes in taste memory seem to be associated with an altered temporal processing. Longer taste-illness delays can be introduced for acquisition of conditioned taste aversions and the modulation of taste learning by the temporal context is absent in naïve aged rats. Evidence is presented suggesting that hippocampal-dependent taste memory can be reactivated by previous learning experiences in old rats. As long as temporary hipocampal inactivation might represent a better model than permanent damage of the aged hippocampus, reversion inactivation of the dorsal Hippocampus by tetrotodoxin (TTX) has been applied in aged rats. Results are reported indicating the need of taking into account the interactions between the previous experiences and acute brain intervention when applying taste learning and memory tasks at advanced ages.